Millennials Killed the Video Star : MTV's Transition to Reality Programming - Klein, Amanda Ann, 1976- (Book collections on Project MUSE., 2021)
"Millennials Killed the Video Star examines the historical, cultural, and industrial factors leading to MTV's shift away from music videos and into identity-focused reality programming in the early 2000s and 2010s"--